{Effect of Yoga-Based Interventions for Anxiety Symptoms: A Meta-Analysis of Randomized Controlled Trials} - Zoogman, S.; Goldberg, S.B.; Vousoura, E.; Diamond, M.C.; Miller, L. (Spirituality in Clinical Practice, 2019)
© 2019 American Psychological Association. Anxiety is a common and debilitating condition, which tends to follow a chronic course if left untreated. While studies have provided evidence that yoga is an effective mind-body intervention for a variety of psychological symptoms, more meta-analytic evidence supporting yoga's efficacy specifically for anxiety symptoms is needed. The aim of this study was to investigate the effect of yoga on anxiety symptoms using meta-analytic methods. A systematic search was conducted for randomized controlled trials (RCTs) on yoga and anxiety on electronic databases over key terms. Risk of bias was assessed using the Cochrane tool. Outcome data were extracted from eligible studies, and moderators were coded across studies to indicate differences in study sample, delivery method, and type of dependent variable. Effect size aggregation and omnibus analyses, as well as moderator tests, were performed. A total of 38 RCTs (N = 2,295 adults) met inclusion criteria. Yoga practice had a large and statistically significant effect on anxiety symptoms compared with control conditions (d = 0.80). In subomnibus analyses, statistically significant effects of the yoga intervention were detected on biological measures (d = 0.45), nonanxiety mental health outcomes (d = 0.55), physical health measures (d = 0.45), and mental and physical health outcomes combined (d = 0.65). Significant moderation was found by study location, with the largest effects appearing in Indian samples. Results suggest that yoga significantly decreases anxiety symptoms, while it appears to have an ameliorative effect on psychological symptoms more globally.
Keywords: anxiety; Meta-analysis; RCTs; Review; Yoga